Efektivitas Penerapan Visual Merchandising pada Event PCE untuk Meningkatkan Minat Beli Konsumen di PT. Bintang Permata Sejati - Theresa Arum Viadollorosa; Siti Aminah (MES Bogor, 2025)
This study aims to evaluate the effectiveness of visual merchandising implementation at the Pasuruan City Expo (PCE) event as a strategy to increase consumer purchasing interest at PT Bintang Permata Sejati. The research method uses a descriptive approach through direct observation during a five-month internship. Visual merchandising was applied in booth design, discount promotions, and the use of QRIS payment technology. The results of the study show that this strategy successfully increased purchasing interest by 35%, with the main contributing factors being aesthetic elements, discount promotions, and customer service. This study provides practical guidance for business practitioners in optimizing visual marketing at promotional events.